2014
DOI: 10.1590/0004-282x20140047
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptoms are present in most of the patients with idiopathic normal pressure hydrocephalus

Abstract: Normal pressure hydrocephalus (NPH) is characterized by gait disturbance, dementia and/or urinary incontinence associated with dilation of ventricular system with normal opening cerebrospinal fluid pressure. Wide scientifical evidence confirms association between NPH and psychiatric symptoms. We selected 35 patients with idiopathic normal pressure hydrocephalus from January 2010 to January 2012 in a Brazilian tertiary hospital and performed a formal psychiatric evaluation to identify psychiatric disorders. Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 22 publications
3
27
0
3
Order By: Relevance
“…The three most common findings in that study were apathy (70.3%), anxiety (25.0%), and agitation (17.2%). In another study involving 35 cases, the frequency of psychiatric signs was 71% (5). The most common findings in this study were anxiety, depressive mood, and psychotic signs.…”
Section: Introductionsupporting
confidence: 53%
“…The three most common findings in that study were apathy (70.3%), anxiety (25.0%), and agitation (17.2%). In another study involving 35 cases, the frequency of psychiatric signs was 71% (5). The most common findings in this study were anxiety, depressive mood, and psychotic signs.…”
Section: Introductionsupporting
confidence: 53%
“…Oliveira et al showed that up to 70% of patients with NPH may present neuropsychiatric symptoms, which may be from metabolic impairments in frontal lobe, basal ganglia and thalamus, all of which can be involved in pathophysiology of OS [1][2][3][4][5][6][7][8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, Normal pressure hydrocephalus (NPH) is a syndrome characterized by urinary incontinence, gait disturbance and dementia plus dilation of ventricular system due to disturbance of cerebrospinal fluid (CSF) circulation [1][2][3][4] . There is wide scientifical evidence pointing association between NPH and psychiatric symptoms [1][2][3][4] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,12,14,28,29,33,45 In 1965, Adams et al 2 proposed a triad of symptoms for NPH, consisting of gait disturbance, cognitive impairment, and urinary incontinence. Many other symptoms have been reported, including subsequent apathy, anxiety, depression, 34,39,43 impaired wakefulness, 7,24 and sexual dysfunction, 31 but on our review of the literature, no previous studies have investigated and reported on bulbar dysfunction in NPH.…”
mentioning
confidence: 90%